Study of Platelet-Rich Plasma Injections in the Treatment of Androgenetic Alopecia Through an One-Year Period - Gkini, Maria-Angeliki (J Cutan Aesthet Surg, 2014)
BACKGROUND: Platelet-rich plasma (PRP) is defined as an autologous concentration of plasma with a greater count of platelets than that of whole blood. Its action depends on the released growth factors from platelets. It has been investigated and used in numerous fields of medicine. Recently, PRP has received growing attention as a potential therapeutic tool for hair loss. AIMS: To evaluate the efficacy and safety of PRP injections in the scalp of patients with androgenetic alopecia. SETTINGS AND DESIGN: Prospective cohort study. MATERIALS AND METHODS: 20 patients, 18 males and 2 females, with androgenetic alopecia were enrolled in the study. PRP was prepared using a single spin method (Regenlab SA). Upon activation, it was injected in the androgen-related areas of scalp. Three treatment sessions were performed with an interval of 21 days and a booster session at 6 months following the onset of therapy. STATISTICAL ANALYSIS: Statistical analysis of the data was performed using the Statistical Package for the Social Sciences (SPSS), version 19.0 (IBM, NY, USA). RESULTS: Hair loss reduced and at 3 months it reached normal levels. Hair density reached a peak at 3 months (170.70 ± 37.81, P < 0.001). At 6 months and at 1 year, it was significantly increased, 156.25 ± 37.75 (P < 0.001) and 153.70 ± 39.92 (P < 0.001) respectively, comparing to baseline. Patients were satisfied with a mean result rating of 7.1 on a scale of 1-10. No remarkable adverse effects were noted. CONCLUSIONS: Our data suggest that PRP injections may have a positive therapeutic effect on male and female pattern hair loss without remarkable major side effects. Further studies are needed to confirm its efficacy.